Toward system innovation for more sustainable chemistry: insights into consumers’ perceptions, knowledge, and behavior related to traceability and product design strategies along leather supply chains - Eisen, Charis; Schenten, Julian; Theis, Anna; Rehn-Groenendijk, Jonas; Helferich, Marvin; Müller, Helena; Hanss, Daniel (Frontiers in Sustainability, 2024)
The leather industry is a complex system with multiple actors that faces a fundamental transition towards more sustainable chemistry. To support this process, this article analyzes challenges of the industry and consumers' roles as a nexus of transition-relevant developments. We present findings of an empirical study (N = 439) among consumers on their perception of leather, related knowledge, and purchasing behavior. We found that participants perceived leather as natural, robust, and of high quality. Knowledge about the manufacturing of leather products was overall limited but varied. Applying a psychological behavior theory, we found that being aware of environmental and health consequences from conventional manufacturing of leather products was positively associated with a personal norm to purchase leather products that are less harmful to environment and health. The perceived ease of buying such products was positively associated with their purchase. Our findings shed light on consumers' roles in the current leather system and their support of niche innovations toward more sustainable chemistry. Against this backdrop, we discuss implications for product design, consumer information, and needs for traceability along supply chains. 1 1 One may -for example, on the grounds of a deontological ethic -fundamentally oppose the exploitation of animals by dairy, meat, and leather industries. However, shifting away from these industries entirely implies an enormous transformation that is beyond the scope of this paper. Instead, we focus on the question of how a transition of the leather industry that minimizes its negative consequences -especially those of problematic chemicals -can be achieved. 2 The structure of our manuscript diverges slightly from the typical structure of other articles normally found in this journal. Our research questions are derived from and feed into system analyses as part of a transformative research process conducted together with practitioners and researchers from various disciplines. While our study contributes to literature in the field of pro-environmental behavior, consumer research, and system innovation, our main focus is to answer practical questions relating to system transition processes.